Isolation and detection of Corynebacterium pseudotuberculosis in the reproductive organs and associated lymph nodes of non-pregnant does experimentally inoculated through intradermal route in chronic form - Abdul Latif, Nur Amirah; Abdullah, Faez Firdaus Jesse; Othman, Aishatu Mohammed; Mohd Nordi, Nur Adza Rina; Lim, Eric Teik Chung; Saad, Mohd Zamri; Saharee, Abdul Aziz; Haron, Abd Wahid; Mohd Lila, Mohd Azmi (Veterinary World, 2015)
Aim: Corynebacterium pseudotuberculosis is the etiological agent of caseous lymphadenitis that affects sheep and goats. This study was designed to determine the presence of the causative organism in the female reproductive organs and associated lymph nodes in non-pregnant does experimentally inoculated through intradermal route in the chronic form. Materials and Methods:18 non-pregnant healthy Katjang does aged 2-year-old were divided randomly into two groups. The first and second group consists of nine non-pregnant does each and the two groups were subdivided into three subgroups. The first group was experimentally inoculated with 1 ml of 107cfu of live C. pseudotuberculosis through intradermal route, whereas the second group was inoculated with 1 ml phosphate buffer saline (pH 7) solution intradermally. The first group were further subdivided into three subgroups where, the first subgroup (B1) were kept for 30 days post-infection, second subgroup (B2) were kept for 60 days post-infection, and third subgroup (B3) were kept for 90 days. The second group was further subdivided into three subgroups (C1, C2, and C3) where they were kept for 39, 60, and 90 days post-infection, respectively. Results: From this study, there was successful isolation of C. pseudotuberculosis from the reproductive organs of the treatment group after 60 days post-infection. The subgroups (B1, C1, C2, and C3) did not show any presence of the causative organism in the reproductive organs. The second subgroup B2 and third subgroup B3 showed positive isolation of the causative organisms from the ovary, uterine horns, uterus, cervix, vagina, and inguinal lymph node of the experimental non-pregnant does. Conclusion: This study showed that chronic infection of C. pseudotuberculosis via intradermal route may cause effect toward the reproductive organs and may be able to influence the reproductive efficiency of the infected animals.